A survey of attitudes towards the curriculum for clinical medicine postgraduates pursuing professional master’s degrees: perspectives of supervisors and students - Xu, Rui; Wu, Jing; Jin, Xin; Tang, Min; Pang, Caishuang; Yang, Zhu; Yu, Huarong (Frontiers in Medicine, 2024)
Background: Based on the recommendation of the Ministry of Education in China to differentiate between "academic" and "professional" degrees, medical schools offer both professional and academic degrees for postgraduates. In China, clinical postgraduates who are pursuing a professional master's degree also participate in standardized residency training (SRT). However, little attention has been given to feedback from students and supervisors regarding postgraduate curricula. Methods: An online questionnaire was designed for clinical postgraduates with professional master's degrees and their supervisors at Chongqing Medical University (CQMU), China. A total of 544 questionnaires from postgraduates and 220 questionnaires from supervisors were included for analysis. Results: Regarding the positive effect of public courses on professional research, 20.04% of clinical professional master's degree students reported "a significant positive effect". Compared with public courses, more postgraduates (33.46%) reported that professional courses had a "significant positive effect" on clinical work (χ 2 =25.00, P<0.05). A total of 49.64% of respondents with clinical professional master's degrees reported at least some repetition between postgraduate public courses and undergraduate courses. Of the postgraduates, 47.43% preferred online learning for public courses, whereas supervisors tended to prefer mixed online and offline learning. A total of 66.73% of postgraduates and 64.55% of supervisors suggested that public alternative courses should be offered to meet the needs of postgraduates. "Mental and health emotion management" and "employment and entrepreneurship guidance" were the public alternative courses that were most strongly preferred by both postgraduates and supervisors. With respect to improvements in selfknowledge and ability through different forms of professional learning, the responses of postgraduates and supervisors differed. According to postgraduates, the most effective type of learning was "participation in research projects", whereas supervisors believed that "professional courses" were most effective. Conclusion: There are differences between clinical postgraduates pursuing professional master's degrees and their supervisors in terms of attitudes towards public and professional curricula. The results of this study may provide guidance to improve public and professional curricula for clinical professional master's degree students.